1989
DOI: 10.1016/s0010-9452(89)80017-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Right Hemisphere in Recovery from Aphasia. Two Case Studies

Abstract: We report two female patients who became global aphasic following a large left hemisphere lesion. With passage of time they recovered to a considerable extent, but three years and six months, respectively, after the former CVA, a new stroke lateralized to the right hemisphere occurred and they showed a definite worsening of language disturbances. Possibilities and limits of the right hemisphere in "taking over" language functions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 25 publications
4
80
1
2
Order By: Relevance
“…Since the 1870's, some reports have suggested that the RH can support some recovery of language after LH stroke (Barlow, 1877;Basso, Gardelli, Grassi, & Mariotti, 1989;Gowers, 1886;Kinsbourne, 1971). Some functional imaging studies have observed RH activation during different language tasks in a variety of aphasia patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1870's, some reports have suggested that the RH can support some recovery of language after LH stroke (Barlow, 1877;Basso, Gardelli, Grassi, & Mariotti, 1989;Gowers, 1886;Kinsbourne, 1971). Some functional imaging studies have observed RH activation during different language tasks in a variety of aphasia patients.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Patients with small left hemisphere lesions may recruit perilesional areas with some involvement of right hemisphere homotops, 7,8,[11][12][13] while recovery for those with larger left lesions may occur entirely via the right hemisphere. [14][15][16][17][18][19][20][21] However, some studies have suggested right hemisphere remodeling as a maladaptive mechanism or epiphenomenon. 22,23 In the current study, we examine the contribution of the right hemisphere to fluency recovery by relating white matter integrity of right speech-motor homotops and the corpus callosum (CC) to a patient's arcuate fasciculus (AF) lesion load (LL) and chronic speech fluency measures.…”
mentioning
confidence: 99%
“…Evidence from patient data also supports this 'map extension' (Thompson, 2000a) with reports of renewed language impairments in people with aphasia with previously recovered language function, but who go on to experience a second left hemisphere stroke (Basso, Gardelli, Grassi, & Mariotti, 1989). Neuroimaging studies have also demonstrated activation of perilesional tissue adjacent to the lesioned area in response to language processing (Heiss, Kessler, Thiel, Ghaemi, & Karbe, 1999;Kurland et al, 2004;Warburton, Price, Swinburn, & Wise, 1999).…”
Section: Stages Of Recoverysupporting
confidence: 58%
“…As far back as 1877, Barlow demonstrated a transference from typical language centres to the right hemisphere (as cited in Crosson et al, 2007). Furthermore, patients with recovered language function following a left hemisphere stroke have been shown to experience a relapse after experiencing new right hemisphere damage (Basso et al, 1989;Thompson & den Ouden, 2008).…”
Section: Stages Of Recoverymentioning
confidence: 96%